2019
DOI: 10.1242/jcs.228973
|View full text |Cite
|
Sign up to set email alerts
|

Monoallelic, antisense and total RNA transcription in an in vitro neural differentiation system based on F1 hybrid mice

Abstract: We developed an in vitro system to differentiate embryonic stem cells (ESCs) derived from reciprocally crossed F1 hybrid mice into neurons, and used it to investigate poly(A)+ and total RNA transcription at different stages of cell differentiation. By comparing expression profiles of transcripts assembled from 20 RNA sequencing datasets [2 alleles×(2 cell lines×4 time-points+2 mouse brains)], the relative influence of strain, cell and parent specificities to overall expression could be assessed. Divergent expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 72 publications
1
14
0
Order By: Relevance
“…Information on the comparative genomic variations was made available in a public database named NIG_MoG (Takada et al 2015 ). The data on single nucleotide polymorphisms (SNPs) in MSM and JF1 has been widely used to identify allele-specific markers for epigenetic and gene expression analyses in commonly used laboratory strains (Yagi et al 2017 , 2019 ; Kondo et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Information on the comparative genomic variations was made available in a public database named NIG_MoG (Takada et al 2015 ). The data on single nucleotide polymorphisms (SNPs) in MSM and JF1 has been widely used to identify allele-specific markers for epigenetic and gene expression analyses in commonly used laboratory strains (Yagi et al 2017 , 2019 ; Kondo et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most genes that is subject to the genomic imprinting control have important roles in regulating the development of individuals and the activities of living organisms [ 27 ]. It has been demonstrated that monoallelic expression of RNAs can be analyzed by using the F1 hybrid mice between B6 and MSM [ 28 ]. In the hybrid F1, there are several genes that show different expression patterns compared to fathers and mothers.…”
Section: Discussionmentioning
confidence: 99%
“…In the hybrid F1, there are several genes that show different expression patterns compared to fathers and mothers. For example, incompatibility due to strain difference occurs due to factors such as mismatching combinations of transcription regulatory factors [ 28 ]. To analyze the incompatibility, it is important to know the normal expression pattern and the proposed method based on the SNPs are useful for such analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic imprinting is one of the most intriguing phenomena of gene expression regulation in mammals. To understand its mechanisms, research has used F1 offspring between two genetically distant inbred mouse strains; our group has analyzed genomic imprinting in F1 hybrid mice from a cross between the C57BL/6 (B6) and MSM/Ms (MSM) strains [ 1 , 2 , 3 ]. This experimental system allowed us to discern the maternal and paternal allele expression by using SNPs on each strain’s chromosomes.…”
Section: Introductionmentioning
confidence: 99%
“…This experimental system allowed us to discern the maternal and paternal allele expression by using SNPs on each strain’s chromosomes. We have also established an in vitro neurogenesis system based on F1-blastocyst-derived embryonic stem (ES) cells [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%